Les Libéraux du "Journal des débats" et de la "Revue des deux-mondes" face aux premières réformes impériales, 1860--1861 - Boudrias, Jean Marc (University of Ottawa (Canada), 1976)
Abstract not available.
Keywords: History, European.; Mass Communications.